Pesticides residue analysis in yam from selected markets across Ghana and Belgium: an evaluation of the QUECHERS method - Abukari Wumbei (International Journal of Food Contamination, 2018)
Abstract Background In recent years, concerns have been raised in Ghana regarding the use of pesticides in yamproduction to the extent that it is feared that pesticides residues may be found in the yam tuber which isconsumed by many Ghanaians. This present study, therefore, was designed to assess the level of pesticides residues in yam bought from across Ghanaian markets i.e. production for local consumption and from Belgium grocery shops (export production from Ghana) using the Quick, Easy, Cheap, Efficient, Rugged and Safe (QuEChERS) method coupled with LC-MS/MS. A total of 180 yam samples, including 150 from Ghana and 30 from Belgium were collected and pesticides residues were analyzed using a multi-residue method. Results A total of 25 pesticides were screened in the yam samples and 11 of them were detected. Theresults indicated that about 46% of the samples contained one or more of the 11 detected pesticides in arange of 0.000014 mg/kg up to 0.0146 mg/kg. The three most detected pesticides in this study were fenpropimorph, cadusafos and fenitrothion, occurring in 179, 171 and 126 samples respectively. All the detected pesticides were below their respective EU maximum residue limits (MRL). Conclusion By these results, it can be said that, the residues of the monitored pesticides found in yam arevery low and are unlikely to pose a negative human health effect.